2019
DOI: 10.31234/osf.io/sj627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Personality Predict Students' Academic Anxiety when Counseling Practice?

Abstract: Many factors are related to students' academic anxiety when learning in class. This research is based on the phenomenon of some students who have difficulty and anxiety in counseling practice classes. The focus of this study is to predict students' academic anxiety based on their personality traits. Ten Item Personality Inventory (TIPI) and Academic Test Anxiety (ATA) was administered to 103 counselors-in-training and analyzed using multiple regression. The results showed that only Extraversion (β = -0.21, p &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The results identified within this scope found that students with high academic anxiety have a disadvantage due to negative personality traits, while positive personality traits play an important role in reducing the effects of academic anxiety. For example, individuals with high academic anxiety have weaker social relationships, lower levels of self-regulation strategies, negative personality traits, and psychological resilience and self-esteem are negatively impacted by their experience of anxiety (Kumari 2010, Cassady et al 2019, Kurniawan et al 2019, Yang et al 2019, Kayani et al 2020, Kayani et al 2021, Dobos et al 2021. Hence, when studies investigating the relationship between mental health variables with academic anxiety are examined, academic anxiety was high in those exposed to a variety of trauma in the childhood period and academic anxiety experienced by individuals with mental health problems like depression and aggression predicted this situation (Katarina 2018, Dobos et al 2021.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results identified within this scope found that students with high academic anxiety have a disadvantage due to negative personality traits, while positive personality traits play an important role in reducing the effects of academic anxiety. For example, individuals with high academic anxiety have weaker social relationships, lower levels of self-regulation strategies, negative personality traits, and psychological resilience and self-esteem are negatively impacted by their experience of anxiety (Kumari 2010, Cassady et al 2019, Kurniawan et al 2019, Yang et al 2019, Kayani et al 2020, Kayani et al 2021, Dobos et al 2021. Hence, when studies investigating the relationship between mental health variables with academic anxiety are examined, academic anxiety was high in those exposed to a variety of trauma in the childhood period and academic anxiety experienced by individuals with mental health problems like depression and aggression predicted this situation (Katarina 2018, Dobos et al 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Purposes f % Sharma and Jaswal 2002, Bhansali and Trivedi 2008, Kumari 2010, Mahato and Jangir 2012, Attri and Neelam 2013, Kumar 2013, Aparnath 2014, Banga 2014a, Banga 2014b, Das et al 2014 Jha 2014, Shakir 2014, Sharma 2014, Siddiqui and Rehman 2014, Mahajan 2015, Thakur and Kumar 2015, Ahuja 2016, Banga 2016, Babu and Zeliang 2017, Gul 2017, Njue and Anand 2018, Rani 2017, Sharma 2017, Hasan 2018, Jabeen and Andrabi 2018, Kaur and Chawla 2018, Yang et al 2019 Determination of differentiation based on demographic variables (age, sex, socioeconomic level, place of residence) 27 44.3 Grover and Smith 1981, Gillen-O'Neel et al 2011, Etiafani and Listiara 2015, Ahuja 2016, Jan et al 2017, Sati and Vig 2017, Hasan 2018, Njue and Anand 2018, Cassady et al 2019, Kurniawan et al 2019, Yang et al 2019, Kayani et al 2020, Kayani et al 2021, Kumari 2010, Li et al 2020, Dobos et al 2021 Correlation with personal psychology variables 17 27.9 Gillen-O'neel et al 2011, Mahato and Jangir 2012, Sharma 2014, Siddiqui and Rehman 2014, Mahajan 2015, Thakur and Kumar 2015, Babu and Zeliang 2017…”
Section: Table 1 Data About Purposes Of Academic Anxiety Studies Studiesmentioning
confidence: 99%
See 1 more Smart Citation